The role of personality on life-long learning of foreign language in online context - Ku, Chen Jung; Rizal Hamid; Anath Rau, Krishnan; Hanudin Amin; Mohamad Isa Abd Jalil; Loi, Chek Kim (Association for Computing Machinery, 2023)
The purpose of this research is to develop a model that clarifies the role of personality traits, motivation, and lifelong learning in the context of distance learning. Specifically, the current study hypothesis that personality traits of extroversion, agreeableness, consciousness, neuroticism, and openness correlate significantly with individuals’ attitudinal-behavioral disposition of motivation, which would also impact lifelong learning. Due to the dynamic process of learning foreign languages and the belief that fluency in other languages offers economic benefits and practical applications, foreign language learning provides a suitable context for the present study. Therefore, we hypothesize that individuals who learn foreign languages are also the most likely to engage in lifelong learning. In addition, the data is collected by the fully online learning system as a result of the Covid 19 disease’s spread. This makes the study even more meaningful to the study of online learning and distance education. In the present study, seven latent variables are developed and tested, totaling 45 measurement items. The survey is conducted to 200 undergraduates from east Malaysia, and only students currently enrolled in foreign language courses will be chosen as respondents. The PLS-SEM will be used to analyzing the data, and we employ two-stage approach for data analysis: (i) measurement model and (ii) analysis of the structural model. The work will provide critical information and practical contributions in line with the Malaysia National Higher Education Strategic Plan—promoting the culture of lifelong learning in on-line context.